What do you know about audit quality in Malaysian small and medium audit firms? / Nur Amira Rodzi and Aida Hazlin Ismail - Rodzi, Nur Amira; Ismail, Aida Hazlin (Universiti Teknologi MARA, 2021)
Audit quality has been addressed and is being discussed globally, throughout the years. The Enron Corporation and World Com cases have affected the reputation of the audit profession. The credibility of auditors also has become more questionable as the auditors’ function in identifying mistakes and fraud is being debated by the public. However, the issue of audit quality has only focused on big firms only. There is shortage of studies that focussed on audit quality in small and medium audit firms. In line with this issue, this study aimed to investigate the relationship between top management support, auditor’s experience and auditor’s accountability on audit quality among st small-medium audit firms in Malaysia. By employing the Attribution Theory, the study utilized purpose sampling. The data used in this study was primary data obtained through questionnaires from external auditors in small and medium sized audit firms around Klang Valley. A total of 100 questionnaires were distributed and the number of usable questionnaires was 81. Findings indicate that auditor’s experience and auditor’s accountability have a significant effect on audit quality. This research thus contributes to standard setters, regulators, policymakers and other audit firms by providing evidence with regard to the determinants of audit quality judgment in Malaysian small and medium audit firms.